Decontamination of prions in a plasma product manufacturing environment. Issue 4 (27th August 2013) - Bellon, Anne; Comoy, Emmanuel; Simoneau, Steve; Mornac, Sandrine; Dehen, Capucine; Perrin, Audrey; Arzel, Aude; Arrabal, Samuel; Baron, Henry; Laude, Hubert; You, Bruno; Deslys, Jean‐Philippe; et al.
<x xml:space="preserve">Abstract</x> Background The high resistance of prions to inactivating treatments requires the proper management of decontaminating procedures of equipment in contact with materials of human or animal origin destined for medical purposes. Sodium hydroxide (NaOH) is widely used today for this purpose as it inactivates a wide variety of pathogens including prions. Study Design and Methods Several NaOH treatments were tested on prions bound to either stainless steel or chromatographic resins in industrial conditions with multiple prion strains. Results Data show a strong correlation between inactivation results obtained by immunochemical detection of the prion protein and those obtained with infectivity assays and establish effective inactivation treatments for prions bound to stainless steel or chromatographic resins (ion exchange and affinity), including treatments with lower NaOH concentrations. Furthermore, no obvious strain‐specific behavior difference was observed between experimental models. Conclusion The results generated by these investigations show that industrial NaOH decontamination regimens (in combination with the NaCl elution in the case of the chromatography process) attain substantial prion inactivation and/or removal between batches, thus providing added assurance to the biologic safety of the final plasma‐derived medicinal products.